The role of polyphenols in atopic dermatitis: a literature review - Angelina Clara Alverina; Maichika Susanto (Indonesian Nutrition Association, 2024)
Background: Atopic dermatitis (AD) is a chronic inflammatory skin with the appearance of pruritic eczema lesions, mostly found in young children, and impact their quality of life (QoL). In concordance with numerous treatment options, some adverse effect might. Recently, it has been discovered that polyphenols may provide satisfactory results for AD therapy and patient’s QoL. Objectives: This literature review objective to summarize recent research the use of polyphenols for AD therapy. Methods: This is a literature review. Literature search was conducted in Pubmed, EBSCOHOST, Proquest, and Google Scholar, using keywords: “atopic dermatitis”, “atopic eczema” and “polyphenols”. Inclusion criteria were: 1) Randomized clinical trials, case reports, case series, literature reviews, systematic reviews, meta-analysis, cohorts, and experimental studies, 2) Available in full text, 3) Written in English, 4) Research studies with intervention conducted in human, 5) Research studies from early 2000s . While article with lack of available data is excluded. The author use Dermatology Life Quality Index (DLQI) to assess the role of polyphenols in QoL for AD. Results: The use of polyphenols in AD shows satisfactory results through their antioxidant, anti-allergic and anti-inflammatory properties. Several studies have observed improvements in sleep disturbance scores, itchiness, and levels of skin moisture and elasticity levels in patients with AD. Conclusions: Polyphenols use in AD provide satisfactory results in reducing symptoms that interfere with QoL. However, due to the limited number of studies conducted on human, further studies of larger-scale participants are needed to confirm the effect of polyphenols in AD treatment.